Blogging and the Transformation of Legal Scholarship - Lawrence B. Solum (Washington University Law Review, 2006)
Will blogging somehow transform legal scholarship? That is the wrong question. The thesis of this essay is that blogging is essentially epiphenomenal—an effect and not a cause. Blogging is merely a particular medium—a currently popular form of Web-based publishing. Nonetheless, the emergence of academic legal blogging is an important indicator of other trends—real causes that are driving significant transformative processes. These trends include the emergence of the short form, the obsolescence of exclusive rights, and the trend toward the disintermediation of legal scholarship. Those forces and their relationship to blogging will be the primary focus of this paper.
Keywords: Law -- Study & teaching; Blogs; Legal scholarship